Implementation of the regional program supports of non-governmental organizations on improvement of the ecological situation of the Karaganda region - Мukasheva, М.А.; Мukasheva, G.Zh.; Arymbekova, А.K.; Surzhikov, D.V. (KSU publ., 2017)
This article is devoted to implementation of programs of local governments which in all countries is very closely connected with environmental issues. Reforming of the ecological legislation is impossible without their participation. The first step of formation of local governments are cooperatives of owners of apartments, agricultural cooperatives and associations to the earth - and water users. Local governments according to the legislation of Kazakhstan have the privilege to use of the natural resources located in their territory and without fail coordinate transfer of rights of such use to other legal entities and individuals. The common system faults depend on horizontal communications in the ecological legislation and with the adjacent, industry legislation. These shortcomings were repeatedly emphasized with national experts at various seminars.
Қарағанды облысының экологиялық жағдайын жақсартуға бағытталған үкіметтен тыс ұйымдардың өңірлік бағдарламасын іске асыру
Реализация региональной программы поддержки неправительственных организаций по улучшению экологической ситуации в Карагандинской области
Keywords: Karaganda region; ecological state; environmental protection; ecopolicy; industrial district; chemical contamination; natural resources